2000
DOI: 10.1111/j.1349-7006.2000.tb00989.x
|View full text |Cite
|
Sign up to set email alerts
|

A Single Nucleotide Polymorphism in the Matrix Metalloproteinase‐1 Promoter in Endometrial Carcinomas

Abstract: Recent studies demonstrated that a single guanine insertion polymorphism in a matrix metalloprotease‐1 promoter created an Ets binding site and affected the elevation of the transcriptional level of matrix metalloproteinase‐1 (MMP‐1). Furthermore, in tumor cell lines derived from melanoma and breast cancer, the incidence of the 2G/2G genotype was significantly higher than that in the normal population. To evaluate the contribution of this polymorphism in endometrial carcinomas, we genotyped 100 endometrial car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 7 publications
4
66
0
1
Order By: Relevance
“…Our results showed no obvious LOH between the gDNA compared to the tumour-derived DNA in 100% of the randomly selected samples (n ¼ 61; data not shown) and this was comparable to other studies in renal (Hirata et al, 2003) and endometrial (Nishioka et al, 2000) carcinomas.…”
Section: Loss Of Heterozygozitysupporting
confidence: 91%
See 2 more Smart Citations
“…Our results showed no obvious LOH between the gDNA compared to the tumour-derived DNA in 100% of the randomly selected samples (n ¼ 61; data not shown) and this was comparable to other studies in renal (Hirata et al, 2003) and endometrial (Nishioka et al, 2000) carcinomas.…”
Section: Loss Of Heterozygozitysupporting
confidence: 91%
“…The discovery of polymorphisms in MMP promoters that alter gene expression has revealed strong associations between these genetic variants and increased susceptibility to the development of malignancies and other diseases (Henney et al, 2000;Ye, 2000). The most extensively studied MMP SNP in relation to cancer is the À1607 bp insertion/deletion in the MMP-1 promoter (Rutter et al, 1998;Nishioka et al, 2000;Ghilardi et al, 2001;Zhu et al, 2001;Hinoda et al, 2002;Tower et al, 2002;Wyatt et al, 2002;Zinzindohoue et al, 2005;Elander et al, 2006). Similar studies have been conducted for the MMP-2 (Miao et al, 2003) and MMP-3 (Ghilardi et al, 2002;Hinoda et al, 2002) gene promoter polymorphism in relation to disease susceptibility and metastatic behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The presence of the additional guanine nucleotide at position 21607 in the MMP-1 promoter was discovered in a highly invasive melanoma cell line and since has been studied in several types of cancer. Cancers that have been examined for the MMP-1 promoter genotype include melanoma, 23 lung, 20 renal cell carcinoma, 21 cervical carcinoma, 27 oral squamous carcinoma, 28 breast, 24,29 ovarian, 18,25 endometrial carcinoma 30 and colorectal carcinoma. 19 In all but 2 studies (breast cancer 29 and melanoma), there was a significant difference in the distribution of the genotypes between the control population and the tumor population.…”
Section: Discussionmentioning
confidence: 99%
“…24 Previous studies reported a higher frequency of the 2G allele in patients with ovarian, endometrial, lung and colorectal cancers and malignant melanoma than in healthy controls, which suggests an association between cancer risk and MMP1 promoter polymorphism. [25][26][27][28][29][30] Recently, it has been reported that LMP1 induces MMP1 in transfected cell lines. The localized expression of MMP1 in NPC tissues has been also detected.…”
mentioning
confidence: 99%